Global burden of periodontal diseases among the working-age population from 1990–2021: results from the Global Burden of Disease Study 2021 - Haojie Fu; Xinyu Li; Ruhong Zhang; Jiaxue Zhu; Xudong Wang (BMC Public Health)
Abstract Background Periodontal diseases among working-age individuals (15–69 years) represent a significant global health challenge, impacting oral health, quality of life, and economic productivity. Defined according to the 2021 Global Burden of Disease (GBD) framework, periodontal disease in this study encompasses symptoms such as halitosis, altered taste sensation, and occasional gingival bleeding that do not impair daily activities. Despite their prevalence, comprehensive analyses of the global burden of periodontal diseases specifically within this demographic remain limited. Methods We analyzed data from the GBD 2021 study, examining periodontal disease burden among individuals aged 15–69 years across 204 countries and territories from 1990 to 2021. Age-standardized rates of prevalence, incidence, and disability-adjusted life years (DALYs) were calculated. We employed joinpoint regression analysis to assess temporal trends, decomposition analysis to examine contributing factors, and frontier analysis to evaluate the relationship between disease burden and sociodemographic development. Findings. In 2021, global periodontal disease cases reached 951.3 million (95% UI: 729.0–1,183.3 million), with an age-standardized prevalence rate (ASPR: 17,011.6 per 100,000 persons) and 80.3 million new cases (ASIR: 1,464.7 per 100,000). The burden accounted for 6.2 million DALYs globally (age-standardized DALY rate: 110.8 per 100,000). Asia demonstrated the highest age-standardized rates across all metrics, while Low-middle SDI regions showed the highest ASPR (20,920.5 per 100,000) and ASIR (1,627.9 per 100,000). At the national level, Sierra Leone, Gambia, and Cabo Verde had the highest disease burden. Males consistently showed higher prevalence rates than females, with peak rates observed in the 50–59 age group. Joinpoint regression analysis revealed an overall increasing trend from 1990 to 2021 (AAPC: 0.04, 95% UI: 0.01–0.06), with notable variations across different time periods. While some countries like Qatar, UAE, and Jordan experienced over 500% increase in prevalence since 1990, Pacific island nations like Tonga and Tokelau achieved reductions exceeding 70%. Decomposition analysis identified population growth (74.56%) and aging (23.00%) as primary drivers of increased disease burden. Interpretation. Our analysis reveals significant global disparities in periodontal disease burden among the working-age population, with concerning increases in many regions from 1990 to 2021. The disproportionate burden in Low-middle SDI regions and South Asia, coupled with the substantial impact of population growth and aging, highlights the urgent need for targeted interventions. While some countries have achieved remarkable reductions in disease burden, the dramatic increases in others underscore the importance of strengthening preventive oral healthcare systems and addressing socioeconomic determinants. These findings emphasize the need for country-specific strategies, particularly in regions with rising burden, and can inform evidence-based policy making to reduce the impact of periodontal diseases on the global workforce.